Evolution of Ecological Thinking in Architectural Theory and Sustainable Design Paradigms - Olimova, Odina; Babakandov, O.N. (Universitas Muhammadiyah Sidoarjo, 2026)
Ecological thinking has increasingly emerged as a central paradigm in contemporary architectural theory, driven by escalating environmental degradation, climate change, and the growing recognition of complex interactions between the built environment and natural systems. Despite the expansion of green and sustainable architecture discourse, prior studies often remain fragmented, focusing separately on environmental performance, materials, or digital tools, without integrating ecological theory, architectural heritage, and technological innovation into a coherent framework. This study aims to systematically examine the evolution of ecological thinking in architectural theory and to clarify its role in shaping sustainable and adaptive design paradigms. The research adopts a qualitative methodology based on systematic literature review, historical–theoretical analysis, and comparative evaluation of architectural paradigms, drawing on peer-reviewed journal articles, theoretical monographs, and recent studies on sustainability, biomimicry, and digital design technologies indexed in major academic databases. The findings reveal a clear paradigm shift from mechanistic and form-oriented architectural models toward holistic, system-based, and interactive ecological approaches, in which architecture is understood as an adaptive component of broader environmental, cultural, and technological systems. The results also demonstrate that digital tools such as Building Information Modeling, data-driven design, and artificial intelligence increasingly support ecological thinking by enabling life-cycle analysis, adaptive responses, and integrative decision-making. The novelty of this study lies in synthesizing ecological theory, traditional architectural knowledge, and contemporary digital technologies into an integrated theoretical perspective, rather than treating them as isolated domains. The implications suggest that ecological thinking should be positioned not merely as an environmental strategy but as a foundational architectural paradigm, informing theory development, guiding sustainable design practice, influencing policy on the built environment, and reshaping architectural education toward interdisciplinary and ecologically grounded curricula.Keywords : Ecological Architectural Theory, Sustainable Design Paradigms, Systems-Based Design, Biomimetic Architecture, Digital Design TechnologiesHighlight : Ecological thinking redefines architecture as integrative systems linking environmental, cultural, technological, and social dimensions. Architectural paradigms shift empirically from mechanistic models toward holistic, adaptive, and system-based ecological frameworks. Digital technologies actively support resource-aware, responsive design, strengthening ecological integration across architectural practice.